TANGGUNG JAWAB NEGARA DALAM PENCEGAHAN DAN PENANGANAN KEKERASAN SEKSUAL DI LINGKUNGAN PERGURUAN TINGGI DALAM PERSPEKTIF HAK ASASI MANUSIA (STUDI PERGURUAN TINGGI DI KOTA PEKANBARU) - Saujani, Ersya Putri; Jayakusuma, Zulfikar; Separen, Separen (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
The policy of the Minister of Education and Culture, which was recently issued inthe form of Minister of Education and Culture Regulation Number 30 of 2021, hasgenerated a lot of perception and even controversy among universities and society itself.This policy is related to the increasing prevalence of sexual violence in the highereducation sector which has a direct or indirect impact on optimizing the Tridharma ofHigher Education which is reduced as well as the quality of Higher Education whichexperiences a decline. All policies or regulations from the government, both from thepresident and from his staff, namely from the ministries, are of course based onconsiderations of various things.Sexual violence in higher education requires special attention from various parties,especially the government as the institution that has the authority to formulate regulationsrelating to sexual violence in higher education. Efforts to protect against sexual violenceare the responsibility of the state which has an obligation to fulfill the human rights ofevery citizen, which includes the academic community. The aim of this research is todetermine the analysis of Minister of Education and Culture Research and TechnologyRegulation No. 30 of 2021 regarding the phenomenon of sexual violence in highereducation environments. The benefit of this research is that the author wants to know howto understand the implementation of the Minister of Education and Culture Regulation No.30 of 2021 and how to understand it from a sociological perspective. This research issociological research obtained from sources related to the PPKS Task Force.The results of this research show that with the increasing number of cases of sexualviolence in higher education environments, this phenomenon ultimately encouraged theMinistry of Education, Culture, Research and Technology to create regulations relating tothe prevention and handling of sexual violence. This regulation was later namedPermendikbud Ristek (Regulation of the Ministry of Education, Culture, Research andTechnology) No. 30 of 2021. Therefore, Ministry of Education, Culture, Research andTechnology Regulation No. 30 of 2021 is a follow-up to the government's seriousness inhandling cases of sexual violence in higher education environments.Keywords: Sexsual Violence, Higher Education, Minister of Educations, ResearchCulture and Technology.